The Effect of Sunnah Fasting on Blood Pressure and Oral Hygiene Level - Erlina Sih Mahanani; Hana Aulia Hapsari; Dinda Triani Ahyati (Universitas Muhammadiyah Yogyakarta, 2022)
The Monday-Thursday fasting, as one of the sunnah highly recommended by Rasulullah, can be a key to maintaining health. This research aims to determine the difference in blood pressure and oral health among the santriwati in Madrasah Mu’allimat Muhammadiyah Yogyakarta who have gotten used to doing and those who have not gotten used to doing Monday-Thursday fasting. It is an observational quantitative research using a cross-sectional design. They were 48 santriwati of 14-18 years old as subjects. Blood pressure was measured thrice with a minimum measurement interval of 15 minutes. The dental and oral hygiene level was obtained using the OHI-S measurement index. The students who habitually carried out sunnah fasting had a normal blood pressure of 20.8% (of a total of 27.1%), and all students had a good level of OHI (27.1%). Meanwhile, among students who are not accustomed to fasting, 45.8% had abnormal blood pressure (a total of 72.9%), and the good level of OHI was only 47.9%. The analysis of Mann-Whitney data showed a significant value for the blood pressure category variable of 0.015 and the OHI-S category of 0.015. The significance level of p 0.05 for each measurement variable (blood pressure and OHI-S categories) illustrated that there were differences in blood pressure and oral hygiene among the santriwati who had gotten used to doing and those who had not gotten used to doing Monday-Thursday fasting.